2016
DOI: 10.1111/liv.13146
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of HCV vertical transmission: what factors should be optimized using data mining computational analysis

Abstract: Hepatitis C virus in pregnancy has substantial risk for vertical HCV transmission: High viral load in HCV-positive women increases the risk of HCV transmission to neonates. Screening pregnant women during early stage of pregnancy and optimizing the HCV viral load in HCV-positive women might prevent vertical HCV transmission to neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Using data mining in applied medicine is important to predict factors lead to disease progression or regression in an intelligent technology fashion. [ 18 ] The aim of this study was to investigate LSM and spleen diameter as simple, cheap and non-invasive tools for prediction of EV in CHC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Using data mining in applied medicine is important to predict factors lead to disease progression or regression in an intelligent technology fashion. [ 18 ] The aim of this study was to investigate LSM and spleen diameter as simple, cheap and non-invasive tools for prediction of EV in CHC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Mode of delivery does not represent significant risk factor for HCV vertical transmission; hence, infected HCV pregnant women not advised to have CS unless indicated for other causes, whatever if minded theoretically, exposure to HCV-infected blood as the infant passes through the birth canal during normal vaginal delivery (NVD) may lead to HCV transmission. However, exposure to maternal blood can also occur with CS; accordingly, there is no reason to offer elective caesarean section to HCV-infected parturients [11][12][13][14] , with respect to special circumstances when CS is preferred to NVD, such as membranous rupture and internal fetal monitoring are confirmed to be associated with HCV transmission. CS and its complications were the main cause of death in many developing countries [15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Simple distribution Naïve Bayes and decision tree created by Rapid I version 4.6 emphasized the level of maternal HCV-related vertical transmission; > 3× 10 6 IU should be considered as the high level of vertical prediction, reported in our previous work [13] , and CS should be likely an important route of global HCV transmission especially in developing countries [ Figures 1 and 2]. However, the level of maternal viremia is still a matter of scientific debate in such vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…For detecting HCV infections, Ahmed and others [14] have used the three classification techniques: Decision Trees (DT), Naïve Bayes, and Neural Networks (NN) and they found that the accuracy of the classification techniques depends on the size of the dataset, with Decision Trees technique having the highest percentage of correct predictions of patients who are likely to get HCV. Elrazek and others [15] had used both Decision Tree and Naïve Bayesian methods algorithms for prediction the vertical transmission (from pregnant mothers to new-borns) of HCV in Egypt. The analysis resulted in that the viral load, liver status, invasive techniques, HIV co infection, and immune response are among the most important predictors and they suggested further studies to determine the preventable high risk factors.…”
Section: Related Workmentioning
confidence: 99%